Pricing carbon : the European Union Emissions Trading Scheme - Ellerman, A. Denny; Convery, Frank J.; Perthuis, Christian de. (New York : Cambridge University Press, 2010)
"The European Union's Emissions Trading Scheme (EU ETS) is the world's largest market for carbon and the most significant multinational initiative ever taken to mobilize markets to protect the environment. It will be an important influence on the development and implementation of trading schemes in the US, Japan, and elsewhere. However, as is true of any pioneering public policy experiment, this scheme has generated much controversy. Pricing Carbon provides the first detailed description and analysis of the EU ETS, focusing on the first 'trial' period of the scheme (2005-7). Written by an international team of experts, it allows readers to get behind the headlines and come to a better understanding of what was done and what happened based on a dispassionate, empirically based review of the evidence. This book should be read by anyone who wants to know what happens when emissions are capped, traded, and priced"--Provided by publisher.
"Pricing Carbon provides the first detailed description and analysis of the EU ETS, focusing on the first, 'trial', period of the scheme (2005 to 2007). Written by an international team of experts, it allows readers to get behind the headlines and come to a better understanding of what was done and what happened based on a dispassionate, empirically based review of the evidence. This book should be read by anyone who wants to know what happens when emissions are capped, traded, and priced"--Provided by publisher.
Machine generated contents note: List of figures; List of tables; List of boxes; List of appendices; Frequently used abbreviations; 1. Introduction; 2. Origins and development of the EU ETS; 3. Allowance allocation; 4. Effects of free allocation; 5. Market development; 6. Emissions abatement; 7. Industrial competitiveness; 8. Costs; 9. Linkage and global implications; 10. Conclusions; 11. Annex: the interaction between the EU ETS and European electricity markets; 12. Appendices; 13. Bibliography; Index.
Περιέχει βιβλιογραφία και ευρετήριο.
Keywords: Emissions trading -- European Union countries; Carbon offsetting -- European Union countries